2011
DOI: 10.1002/elan.201100214
|View full text |Cite
|
Sign up to set email alerts
|

Electrogenerated Chemiluminescence Sensor Based on a Self‐Assembled Monolayer of Ruthenium(II)‐bis(2,2′‐bipyridyl)(aminopropyl imidazole) on Gold Deposited Screen Printed Electrode

Abstract: A new electrogenerated chemiluminescence (ECL) sensor based on a self-assembled monolayer (SAM) of Ru(II)-bis(2,2'-bipyridyl)(aminopropyl imidazole) on a gold-deposited screen printed electrode (SPE) has been developed. Since the ECL emission of the Ru(II)-bis(2,2'-bipyridyl)(aminopropyl imidazole) complex can be easily obtained at an applied potential of less than + 0.8 V, the possibility of the oxidation of the Ru-complex SAM formed on gold-deposited SPE electrode surface was greatly diminished and thus the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Many reports have focused on the immobilization of RuBpy, including the Langmuir-Blodgett technological approach [28][29][30], the self-assembly technique [31,32] and the sol-gel method [33][34][35][36]. The immobilization materials for RuBpy have also been applied to sensing, such as cation-exchange polymers [37][38][39], SiO 2 nanoparticles [40][41][42][43], carbon nanotubes [44,45], metal nanoparticles [46] and MOF materials [47]. Among these materials, multi-walled carbon nanotubes (MWCNTs) have excellent electrical conductivity (1.85 × 10 3 S cm −1 ) as a carrier material [48].…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have focused on the immobilization of RuBpy, including the Langmuir-Blodgett technological approach [28][29][30], the self-assembly technique [31,32] and the sol-gel method [33][34][35][36]. The immobilization materials for RuBpy have also been applied to sensing, such as cation-exchange polymers [37][38][39], SiO 2 nanoparticles [40][41][42][43], carbon nanotubes [44,45], metal nanoparticles [46] and MOF materials [47]. Among these materials, multi-walled carbon nanotubes (MWCNTs) have excellent electrical conductivity (1.85 × 10 3 S cm −1 ) as a carrier material [48].…”
Section: Introductionmentioning
confidence: 99%
“…The organosulfur compounds bearing an imidazole (Im) functional group have been used as the linker for a variety of chemical species, which facilitates electrocatalysis toward CO 2 reduction, bioactivity, , corrosion prevention, and sensor and molecular electronics development. , It is shown that the Im group entrapped at an Au electrode in an ionic liquid enables electrocatalytic conversion of CO 2 to CH 3 OH and HCOOH. This is achieved by shuffling a proton from a source to CO 2 via the Im group.…”
Section: Introductionmentioning
confidence: 99%
“…These methods can be classified into general approaches including electrostatic adsorption by cationic exchange polymer such as Nafion [6,7], self-assembled monolayer (SAM) [8,9], doping into nanomaterials [10,11], sol-gel [12] and composite films [13,14]. A direct deposition of the luminescent molecule on the carbon electrodes were also adapted [15,16] which believed to enhance the rate of electron transfer kinetics and avoid problems related to the lack of permeability, conductivity, and uniformity of the host membrane.…”
Section: Introductionmentioning
confidence: 99%